Sosialisasi Pemanfaatan Fisika Radiasi dalam Bidang Kesehatan Kepada Siswa Kelas X di SMA Negeri 1 Lawe Sigala-gala - Ulan Dari; Arivatussaqdiyah; Rahayu Putri; Yaumil Silvini (CV. Armas Suan Sejahtera, 2024)
Initial understanding of a field of science influences students' decisions in choosing a major to continue their studies at university. Physics with a medical concentration is one of the relatively new majors and continues to be developed. The number of job requirements for the medical physicist profession is also relatively high. However, this is not yet supported by the availability of sufficient information regarding the application of physics in the health sector among students of Lawe Sigala-Gala State High School. Therefore, the Physics study program at Gunung Leuser University, Aceh, feels the need to disseminate information about the use of radiation physics in the health sector in the form of a seminar with the aim of increasing students' insight regarding the use of physics to help them determine their choice of further studies at university. The results of this community service show that students' understanding has increased after the community service activity was held. The majority of students also expressed their satisfaction with the activity.